Genome sequence of a human tumorigenic poxvirus: prediction of specific host response-evasion genes - Senkevich, Tatiana G.; Bugert, Joachim J.; Sisler, Jerry R.; Koonin, Eugene V.; Darai, Gholamreza; Moss, Bernard (Science, 1996)
Molluscum contagiosum virus (MCV) commonly causes asymptomatic cutaneous neoplasms in children and sexually active adults as well as persistent opportunistic acquired immunodeficiency syndrome (AIDS)-associated disease. Sequencing the 190-kilobase pair genome of MCV has now revealed that the virus potentially encodes 163 proteins, of which 103 have homologs in the smallpox virus. MCV lacks counterparts to 83 genes of the smallpox virus, including those important in suppression of host responses to infection, nucleotide biosynthesis, and cell proliferation. MCV possesses 59 genes that are predicted to encode previously uncharacterized proteins, including major histocompatibility complex class I, chemokine, and glutathione peroxidase homologs, which suggests that there are MCV-specific strategies for coexistence with the human host.
Gesehen am 22.08.2024